THE EFFECT OF SPORTS IN PROMOTING THE ENHANCEMENT OF ADULT BONE DENSITY - Liu,Feng (2022)
ABSTRACT Introduction: Exercise is an important part of osteoporosis treatment. A moderate amount of exercise can improve bone metabolism, improve bone biomechanics and increase bone density. Objective: To study the effects of different sports on adult bone mineral density. Methods: We selected volunteers to perform different exercises and used quantitative ultrasound and bioelectrical impedance methods to test the volunteers. Results: Exercise can increase the content of lean body mass in body composition and reduce body fat percentage. The calcaneal bone mineral density of physical education students is positively correlated with low body weight. Conclusion: Exercise can promote the bone mineral density of young adults. Stronger weight-bearing exercises can better promote the increase of bone density. Level of evidence II; Therapeutic studies - investigation of treatment results.